Diamond photocathodes in gaseous environments - Foord, J; Bennett, A; Peel, M; Jackman, R (2004)
The performance of UV diamond photocathodes in gaseous environments has been explored with regard to the potential applications, which exist for such devices. Stable performance is exhibited even at gas pressures approximately 0.5 bar for hydrogenated diamond, in gaseous environments such as He, H2, O2, CH4 and CF4. However, for chlorocarbon gases, UV stimulated photodissociation of the ambient gas causes the adsorption of chlorine on the diamond surface, and rapidly degrades device performance. Thermal dissociation of ambient gases brings about a similar effect. Thus, although diamond photocathodes do have potential use in gaseous environments, it is clear that care is required to ensure that the hydrogenated surface layer is not destroyed when in use. © 2003 Elsevier B.V. All rights reserved.